Tooth brushing techniques among pupils attending a Nigerian unity basic school - Adamu, V. E.; Eneojo, N. I. F.; Eze, C. J. (Orapuh Journal, 2020)
IntroductionAdopting a proper tooth brushing technique is the second best choice, after the choice of acquiring the right toothbrush, when it comes to proper daily hygiene. With the proper tooth brushing technique, food debris and dental plaque, which has been implicated in the initiation and progression of the 2 commonest oral diseases – dental caries and periodontal disease, will be eliminated. PurposeThis survey was undertaken to study tooth brushing techniques among pupils attending Unity Primary School, Mgbakwu, Awka-North LGA, Anambra State, Nigeria with a view to enhance the content of oral health education to this category of children in Nigeria.Materials and methods The tooth brushing techniques of a sample of 120 pupils attending the school, selected using the proportionate stratified sampling technique, were investigated. Data was obtained using personal interviews and tooth brushing technique observation. Participants were made up of equal number of male (50%) and female (50%) pupils. Most participants fell between the age range of 9-12 years (52.50%). Information from the survey activities was recorded in a data sheet.ResultsResults of the study indicated that no single pupil used the correct technique of tooth brushing (the roll technique) for their daily oral hygiene (0.00%). Most participants, irrespective of age or gender, adopted the horizontal technique of tooth brushing (85.83%) for their daily oral hygiene. 8.33% used the vertical technique and 5.83%, the circular technique. Further inferential analysis of data indicated that the tooth brushing techniques of the pupils attending the study school were not significantly adequate (p>0.05) and the choice of the technique of tooth brushing was not significantly related to gender or age (p>0.05). ConclusionsThis study shows that the pupils were unaware of the correct technique of tooth brushing. Oral health education, especially on tooth brushing techniques, is an urgently needed oral public health tool to help arrest the unhealthy oral health behavior, which may be catalyzing oral diseases or their precursors in the study population.